The coagulation-time of the blood in disease: some clinical records and considerations - Shafto, W. A. (The University of Edinburgh, 1913)
It is now almost twenty years since Wright first drew attention to the value of measuring the rate of coagulation of the blood in disease. Since then much has been written upon the subject and many new methods of observation have been devised.

Much of the work done in the earlier days was rather of the nature of physiological experiment: but indeed the results obtained by the various methods differed so widely and were so inconsistent even in themselves that there was little encouragement given for an advance to clinical observations. Later, with improved technique (most especially with a due regard to the knowledge of the effect of temperature as a factor in variation) much more reliable and consistent results were obtained and the advance to clinical problems was made with more assurance. Yet even now there are but few records in the literature of research into the coagulation time of the blood in disease. Haemophilia and purpura, it is true, have been studied in some detail, as also the assertions of Wright respecting the value of calcium salt administration (though in this last the examination has been chiefly, as by Addis'' along pharmacological lines) but in other diseases the records are few and imperfect. This comparative scantiness of clinical records has encouraged me to embark upon the series of observations here recorded. They have been arrived at by the uso of yet another method - a method borrowed from Drs. Dale and Laidlaw, as set forth by them in the Journal of Pathology and Bacteriology. ( This for brevity's sake I have termed the "Ball method")